2020
DOI: 10.1186/s10194-020-01100-x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive aging in migraine sufferers is associated with more subjective complaints but similar age-related decline: a 5-year longitudinal study

Abstract: Objectives and background: The effect of headache on cognitive performance is controversial, due to conflicting results obtained from studies in clinical or population settings. We aimed to understand if migraine and other headaches modify the rates of decline on different cognitive measures, during a 5-year interval. Design and method: A cohort of community dwelling adults (> 50 years) with migraine (MH), non-migraine headaches (NMH) and controls without headache (WoH), was assessed by a comprehensive neurops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 61 publications
0
18
1
Order By: Relevance
“…However, it is worth mentioning a recent study showing that migraine and non-migraine headache are not associated with increasing risk of dementia or cognitive decline at an older age although subjects with migraine have more cognitive complaints. 38 However, we did not find a correlation between the measures of migraine severity and efficiency of executive function. Previous studies [39][40][41] have reported similar findings in 42 These genetic polymorphisms were also reported to be related to the susceptibility for migraine, although evidences for such an association were inconsistent.…”
Section: Discussioncontrasting
confidence: 69%
“…However, it is worth mentioning a recent study showing that migraine and non-migraine headache are not associated with increasing risk of dementia or cognitive decline at an older age although subjects with migraine have more cognitive complaints. 38 However, we did not find a correlation between the measures of migraine severity and efficiency of executive function. Previous studies [39][40][41] have reported similar findings in 42 These genetic polymorphisms were also reported to be related to the susceptibility for migraine, although evidences for such an association were inconsistent.…”
Section: Discussioncontrasting
confidence: 69%
“…The overlap of potential biological mechanisms between migraine and dementia, such as neuroinflammation, brain microstructural changes, and subcortical white matter abnormalities, 5‐8 indicates that migraine may increase the risk of dementia. However, current studies that reported an association between migraine and dementia demonstrated inconsistent associations 9,10 …”
Section: Introductionmentioning
confidence: 68%
“…In recent studies, subjective cognitive complaint scores tended to increase with the frequency of migraines with aura, and this interrelation is influenced by depression severity [38]. In a five-year longitudinal study, migraine was not associated with an increased risk of dementia or cognitive decline in older age, but individuals with migraines had more subjective cognitive complaints and depressive symptoms than the control patients did [39].…”
Section: Discussionmentioning
confidence: 93%